An effective approach for network management based on situation management and mashups - Rendon, Oscar Mauricio Caicedo (2015)
The Situation Management discipline is intended to address situations happening or that might happen in dynamic systems. In this way, this discipline supports the provisioning of solutions that enable analyzing, correlating, and coordinating interactions among people, information, technologies, and actions targeted to overcome situations. Over recent years, the Situation Management has been employed in diverse domains ranging from disaster response to public health. Notwithstanding, up to now, it has not been used to deal with unexpected, dynamic, and heterogeneous situations that network administrators face in their daily work; in this thesis, these situations are referred to as network management situations. The mashup technology also allows creating solutions, named mashups, aimed to cope with situations. Mashups are composite Web applications built up by end-users through the combination of Web resources available along the Internet. These composite Web applications have been useful to manage situations in several domains ranging from telecommunication services to water floods. In particular, in the network management domain, the mashup technology has been used to accomplish specific tasks, such as botnet detection and the visualization of traffic of the border gateway protocol. In the network management domain, large research efforts have been made to automate and facilitate the management tasks. However, so far, none of these efforts has carried out network management by means of the Situation Management and the mashup technology. Thus, the goal of this thesis is to investigate the feasibility on using the Situation Management and mashups as an effective (in terms of complexity, consuming of time, traffic, and time of response) approach for network management. To achieve the raised goal, this thesis introduces an approach formed by mashments (special mashups devised for coping with network management situations), the Mashment Ecosystem, the process to develop and launch mashments, the Mashment System Architecture, and the Mashment Maker. An extensive analysis of the approach was conducted on networks based on the Software-Defined Networking paradigm and virtual nodes. The results of analysis have provided directions and evidences that corroborate the feasibility of using the Situation Management and mashups as an effective approach for network management.